2018
DOI: 10.1136/jech-2018-210838
|View full text |Cite
|
Sign up to set email alerts
|

Association of community food environment and obesity among US adults: a geographical information system analysis

Abstract: BackgroundEmerging studies have investigated the contribution of food environment to obesity in the USA. However, the findings were inconsistent. Methodological explanations for the inconsistent findings included: (1) using individual store/restaurant exposure as food environment indicator, and (2) not accounting for non-stationarity assumption. This study aimed to describe the spatial distribution of obesity and examine the association between community food environment and obesity, and the variation of magni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Prior research has established a strong relationship between store access and consumer obesity in socioeconomically disadvantaged areas, 9 which is why it is particularly important to understand such access for SNAP consumers. This study adds to existing literature by characterizing the relationship between obesity prevalence and a wider range of SNAP-authorized stores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has established a strong relationship between store access and consumer obesity in socioeconomically disadvantaged areas, 9 which is why it is particularly important to understand such access for SNAP consumers. This study adds to existing literature by characterizing the relationship between obesity prevalence and a wider range of SNAP-authorized stores.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 This relationship may vary among communities, and additionally, obesity prevalence related to traditional and nontraditional (eg, dollar, drug, and convenience) SNAP-authorized store access is underinvestigated. 7 -9 Exploring a wide range of store associations with community obesity prevalence can inform future food environment research and guide SNAP-Education (SNAP-Ed) healthy food retail programming. 10 This was the purpose of the presented research, using Virginia as a case study due to authors’ practice site location.…”
Section: Purposementioning
confidence: 99%
“…Studies identifying spatial clusters or hotspots of physical activity, sedentary behavior, obesity, and diabetes have been carried out mainly in the United States, while few are reported from low-and middle-income countries. [8][9][10][11][12][13] Despite the high burden of NCDs in India, research incorporating spatial clustering techniques is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This negative relationship has been shown in numerous countries outside of the US (e.g., Netherlands, Turkey, Morocco, South Asia) [103]. Hot-spot analysis in the US shows that higher BMI clusters are more likely in socioeconomically disadvantaged minority neighborhoods [104]. Meanwhile, large datasets (n = 43,864) have shown that obesity risk is decreased when positive contextual factors (maternal mental health, school safety, and child resilience) are present [105].…”
Section: Socioeconomic Statusmentioning
confidence: 86%